Environmental Management Plan And Guidelines For Reaching All Children with Education in Lebanon (R.A.C.E LEBANON) - MEHE (Beirut MEHE, 2015)
UN agencies and development partners, with the support of the Global Partnership for Education (GPE) and led by the Government of Lebanon (GoL), specifically the Ministry of Education and Higher Education (MEHE), committed to implement a project that aims to ensure equitable access to educational opportunities in the public system, improve the quality of the teaching and learning environment, and strengthen national education systems and monitoring. The project has three components: access, quality of learning environment and project management and support. The total estimated cost is US
: Report
Keywords: (RACE); (RACE); (RACE); Educational policy; Politique éducative